2018
DOI: 10.1016/j.dib.2018.04.123
|View full text |Cite
|
Sign up to set email alerts
|

Data on the characterization of non-cytotoxic pyomelanin produced by marine Pseudomonas stutzeri BTCZ10 with cosmetological importance

Abstract: The article focuses on data dealing with characterization of black brown melanin produced by marine bacteria Pseudomonas stutzeri BTCZ10. Figures deal with the production of melanin by strain BTCZ10 and characterization of the pigment using biophysical techniques. Table presents the data on photo-protective ability of melanin when blended with commercial sunscreens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 6 publications
4
13
0
Order By: Relevance
“…The assays were carried out on the three HGA-pigments, along with the two standards (Mel SEPIA , Mel SYNTH ) and common antiradical agents such as Trolox, ascorbic acid, and propyl gallate, all prepared in DMSO. Figure 7 S-A and 7 S-B indicated that Pyo ENZ (EC 50 27.5 µg/mL) and Mel SYNTH (EC 50 25.9 µg/mL) have an antioxidant activity equivalent to that of ascorbic acid (29 µg/mL), as already reported for pyomelanin isolated from Pseudomonas stutzeri strain BTCZ10 and Pseudoalteromonas lipolytica BTCZ28 45 , 46 . The degradation of pyomelanin by enzymes or microorganisms has never been described to date, whereas ascorbic acid is rapidly metabolized and was thought to act as a pro-oxidant when the glutathione pool is depleted 47 , a feature that must also be controlled in the case of pyomelanin.…”
Section: Resultssupporting
confidence: 77%
“…The assays were carried out on the three HGA-pigments, along with the two standards (Mel SEPIA , Mel SYNTH ) and common antiradical agents such as Trolox, ascorbic acid, and propyl gallate, all prepared in DMSO. Figure 7 S-A and 7 S-B indicated that Pyo ENZ (EC 50 27.5 µg/mL) and Mel SYNTH (EC 50 25.9 µg/mL) have an antioxidant activity equivalent to that of ascorbic acid (29 µg/mL), as already reported for pyomelanin isolated from Pseudomonas stutzeri strain BTCZ10 and Pseudoalteromonas lipolytica BTCZ28 45 , 46 . The degradation of pyomelanin by enzymes or microorganisms has never been described to date, whereas ascorbic acid is rapidly metabolized and was thought to act as a pro-oxidant when the glutathione pool is depleted 47 , a feature that must also be controlled in the case of pyomelanin.…”
Section: Resultssupporting
confidence: 77%
“…Fig. 7S-A and 7S-B indicated that PyoENZ (EC50 27.5 µg/mL) and MelSYNTH (EC50 25.9 µg/mL) have an antioxidant activity equivalent to that of ascorbic acid (29 µg/mL), as already reported for pyomelanin isolated from Pseudomonas stutzeri strain BTCZ10 and Pseudoalteromonas lipolytica BTCZ28 45,46 . The degradation of pyomelanin by enzymes or microorganisms has never been described to date, whereas ascorbic acid is rapidly metabolized and was thought to act as a pro-oxidant when the glutathione pool is depleted 47 , a feature that must also be controlled in the case of pyomelanin.…”
Section: Physicochemical Properties (Summarized Insupporting
confidence: 80%
“…Zeng et al (2017) reported the hyperpigmentation of pyomelanin which is a complex of polyphenolic heteropolymer produced under elevated temperature by marine hmgA mutant P. lipolytica displaying anti-fouling activity. Kiran et al (2017) confirmed the anti-microbial activity against S. aureus, B. subtilis, E. coli, and P. aeruginosa displayed strong anti-biofilm activity against MDSA by nano-melanin synthesized by sonication of Pseudomonas sp., isolated from marine sponge T. citrine where the efficiency of nano-melanin was observed to be higher than the traditional melanin.…”
Section: Melaninsupporting
confidence: 57%
“…As a twist Melanin impregnated with copper and iron on its surface proved to be efficient in removing arsenic by chemisorption and it was also noted that melanin exhibited thermostability up to 120 • C and showed peak absorption of arsenic at pH of 4-6 where XPS studies showed that arsenite before binding to Cu-, Fe-Impregnated melanin oxidized to arsenate and finally removing the Cu and Fe by Hcl treatment for the recycling of melanin and again impregnating it with fresh Cu and Fe element for absorption which showed 99% efficiency to 4 absorption and desorption cycles. P. stutzeri BTCZ10 strain was reported to play a photoprotective role by displaying SPF value equivalent to sunscreen showed by Kurian and Bhat (2018). Zeng et al (2017) reported the hyperpigmentation of pyomelanin which is a complex of polyphenolic heteropolymer produced under elevated temperature by marine hmgA mutant P. lipolytica displaying anti-fouling activity.…”
Section: Melaninmentioning
confidence: 99%